Digital Ecosystems in Food Delivery : Analysis of Strategies and Business Models - Forner, Denisa (2024)
The food delivery ecosystem has experienced a strong transformation during the past decade, mainly due to advancements in digital technology and changing consumer behavior. This thesis offers a view of the dynamics of the digital ecosystem within the food delivery sectors in Europe, focusing on key players such as Uber Eats and Deliveroo. The objectives of the thesis are to analyze common business models and strategic approaches and offer potential partnership models. The research uses a missed method approach using both qualitative and quantitative data to provide a comprehensive understating of the current state and future directions. The literature review highlights the importance of digital ecosystems, exploring ways to improve operational efficiency, enhance customer experience, and increase their market share. It discusses several business models, such as the aggregator model, ghost kitchen, and white-label solutions. The review also explores integrations of several logistics strategies, such as AI-based route optimizations and real-time data analysis, which are both important for maintaining competitiveness and efficiency. The primary research was conducted via survey and sent to 33 related participants in order to examine insights on consumer behaviors, preferences, and satisfaction. The main findings show that customers value promotions, real-time tracking, and wide restaurant choices. However, there is a need for improvement in delivery speed and good quality. The study also highlights the importance of digital technology and environmental sustainability in shaping consumer loyalty and overall satisfaction. Based on the findings there, several recommendations were proposed. They include maintaining attractive promotions, optimizing delivery speed, including premium services, investing in digital innovations, and adopting environmentally sustainable practices.